Pendugaan Struktur Bawah Permukaan Gunung Merapi Berdasarkan Analisis Data Anomali Medan Gravitasi Citra Satelit - Uswatun Chasanah; Siti Diah Ayu Febriani; Eko Minarto (Lambung Mangkurat University Press, 2021)
ABSTRACT-Merapi Mount (2978 msl) is the higher active volcanoes in Indonesia, which is located between Sleman district, DI. Yogyakarta, and Magelang district, Boyolali district, Klaten district, Central Java. The eruption center of Merapi Mount is controlled by weak or unstable zone. This weak or unstable zone can be known from several lithologies of rock, which lies below Merapi Mount's surfaces through the density differences. One of the methods for determining the subsurface density in geophysics science is the gravity method. The gravity method is based on the difference in mass below the surface. This research aims to determine the distribution pattern lithology of Merapi Mount based on the density differences. Data processing in this research covers the entire process begins with a reading tool in field to obtain Bouguer anomaly's values at every point. To know the appearance below the Merapi Mount surface, creating some structure lithology modeling using software surfer 10 and Grav2DC. The result obtained in this research indicated that lithology below the surface of Merapi Mount. The variant of rocks density is between 2,256- 3,298 g.cm-3. Most of them are sedimentary rock such as sandstone, granite, and basalt. Where the whole rocks an abundance of cold lava of Merapi Mount.